Advances in lncRNAs from stem cell-derived exosome for the treatment of cardiovascular diseases - Ma, Jiahui; Lei, Pengyu; Chen, Haojie; Wang, Lei; Fang, Yimeng; Yan, Xiaoqing; Yang, Qinsi; Peng, Bo; Jin, Libo; Sun, Da (Frontiers in Pharmacology, 2022)
Cardiovascular diseases (CVDs) are the leading cause of mortality globally. Benefiting from the advantages of early diagnosis and precision medicine, stem cell-based therapies have emerged as promising treatment options for CVDs. However, autologous or allogeneic stem cell transplantation imposes a potential risk of immunological rejection, infusion toxicity, and oncogenesis. Fortunately, exosome can override these limitations. Increasing evidence has demonstrated that long non-coding RNAs (lncRNAs) in exosome from stem cell paracrine factors play critical roles in stem cell therapy and participate in numerous regulatory processes, including transcriptional silencing, transcriptional activation, chromosome modification, and intranuclear transport. Accordingly, lncRNAs can treat CVDs by directly acting on specific signaling pathways. This mini review systematically summarizes the key regulatory actions of lncRNAs from different stem cells on myocardial aging and apoptosis, ischemia-reperfusion injury, retinopathy, atherosclerosis, and hypertension. In addition, the current challenges and future prospects of lncRNAs treatment for CVDs are discussed.